1998
DOI: 10.1152/ajprenal.1998.274.6.f1062
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenesis and angiotensin II receptor subtypes gene expression in the fetal lamb

Abstract: To investigate the role of angiotensin II (ANG II) in nephrogenesis, a developmental study of renal AT1 and AT2 receptor mRNA expression was performed in parallel with the quantitative and qualitative analysis of metanephros development in fetal lamb from 60 to 140 days of gestation. Both ANG II receptor subtypes were expressed early during nephrogenesis but displayed specific spatial and temporal distribution during gestation. High-AT2 mRNA expression took place in the outermost nephrogenic area and in the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 24 publications
4
50
1
Order By: Relevance
“…Fractional glomerular volume is an estimation of total filtration capacity, taking into consideration both glomerular number and volume. Nephron number was not determined in this study, although nephrogenesis in the sheep fetus is near completion at 130 days of gestation (Gimonet et al 1998). These findings confirm those observed in rats where administration of the AT 1 -specific receptor antagonist, losartan, in the first 3 weeks of postnatal life causes a decrease in the absolute and relative size of the kidney (Tufro-McReddie et al 1994).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Fractional glomerular volume is an estimation of total filtration capacity, taking into consideration both glomerular number and volume. Nephron number was not determined in this study, although nephrogenesis in the sheep fetus is near completion at 130 days of gestation (Gimonet et al 1998). These findings confirm those observed in rats where administration of the AT 1 -specific receptor antagonist, losartan, in the first 3 weeks of postnatal life causes a decrease in the absolute and relative size of the kidney (Tufro-McReddie et al 1994).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies in fetal sheep have demonstrated that there are only mature glomeruli present in the developing kidney from 120 days of gestation (Gimonet et al 1998). In this study at 130 days of gestation, all the glomeruli were mature and were identified with a clearly defined capsule and capillary structure.…”
Section: Morphological Analysessupporting
confidence: 46%
See 2 more Smart Citations
“…It also seems likely that the AT 2 receptor is involved in the development of the kidney and urinary tract. [73][74][75] The ACE gene is very widely expressed, perhaps ubiquitously, through the body. 76 While the primary sites of production of renin and of angiotensinogen are respectively kidney and liver, renin and angiotensinogen genes are extensively manifested in other tissues, many of which, as was stated in the preceding section, have been shown to contain renin.…”
mentioning
confidence: 99%